Ethnobotanical Study of Hypertension (High Blood Pressure) Medicinal Plants in Mekarsari Village, Pasir Jambu District, Bandung, West Java - Qotrunnada, Ananda; Widyati, Agustin; Friscilla, Sulastri; Rahayu, Sri Endarti (Journal of Tropical Biodiversity, 2024)
Indonesia is the second richest country in terms of biodiversity, with 35,000 plant species, 3,500 of which are medicinal plants. Generally, people use these plants as traditional medicine passed down through generations, which is the concept studied in the field of Ethnobotany . This study was conducted to obtain information on the use of medicinal plants for treating hypertension and the traditional processing of these plants by the community around Mekarsari Village, Pasir Jambu District, Bandung, West Java. According to data from the West Bandung City Health Office, the most common disease affecting the people of Mekarsari Village is hypertension. The methods used in this study include observation, interviews, field observations, identification, and documentation of medicinal plants as well as residents during interviews. Based on the research, 38 plant species from 25 different families were found to be used as hypertension medicine. The plants with the highest Fidelity Level (FL) values in treating hypertension are three species: Soursop leaves (Annona muricata) at 30%, Bay leaves (Syzygium polyantum) at 25%, and Sintrong leaves (Crassocephalum erepidioides) at 22.5%.